Hydrogen Softening in the Thin Plate of Microcrystalline 316L Stainless Steel. Issue 8 (20th June 2013) - Kim, Yunsung; Shin, Dongjun; Kim, Youngsuk; Kim, Dae Whan; Kim, Sungsoo; Nam, Wonjong; Kim, Yong‐Suk; Máthis, Kristián; Choe, Heeman
Abstract: The thin‐plate specimen of 316L austenite stainless steel was charged with hydrogen using a cathodic charging technique. Despite the short diffusion distance of hydrogen predicted by the diffusion‐controlled model for a semi‐infinite sheet, the Vickers hardness measurements revealed the full effect of hydrogen in the center of the cross‐sections of thin‐plate specimens as well as in the vicinity of the outer surfaces, which appears to be due to the short‐circuit diffusion mechanism along the grain boundaries. The room‐temperature tensile properties of both undeformed and deformed (20, 40%) samples were examined and compared. Hydrogen softening was apparent in both types of samples. For example, the 40% deformed sample showed an approximately 17 and 7% lower yield and tensile strength, respectively, after H charging at a strain rate of 2 × 10 −4  s −1 with a concomitant decrease in ductility compared to that without H. Abstract : 316L austenite stainless steels have attracted considerable attention as advanced structural materials in nuclear power plants. Thin‐plate specimens of 316L are charged with hydrogen using a cathodic charging technique. Despite the short diffusion distance of hydrogen predicted by the diffusion‐controlled model for a semi‐infinite sheet, Vickers hardness measurements and room‐temperature tensile results reveals the full effect of hydrogen in the center of cross‐sections of the thin‐plate specimens as well as in the vicinity of the outer surfaces.